Minds and Machines : A Conversation with Miguel Nicolelis. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Miguel Nicolelis, Professor of Neurobiology, Neurology, Neurosurgery, Biomedical Engineering, Psychology and Neuroscience and Orthopaedic Surgery and Co-Director of the Center for Neuroengineering at Duke University. This thought-provoking conversation dives into Miguel Nicolelis' extensive and important research for over 20 years now and how he has been blurring the line between science fiction and science fact, developing increasingly sophisticated ways of harnessing the thoughts of rats, monkeys and humans to dr.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Revolutionary Rumblings -- II. Plowing Ahead -- III. Interface -- IV. Against Reductionism -- V. Incarnating Our Surroundings -- VI. Imposing Representations -- VII. Distributed vs. Local -- VIII. Technological Applications -- IX. Getting Metaphysical -- X. Final Questions -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Nicolelis, Miguel A. L. -- Interviews; Nicolelis, Miguel A. L; Brain-computer interfaces; Interfaces cerveau-ordinateur.; Neurosurgery; Surgery; MEDICAL; Neuropsychology; PSYCHOLOGY; Biomedical; TECHNOLOGY & ENGINEERING; Brain-computer interfaces; Interviews